2014
DOI: 10.1126/science.1250020
|View full text |Cite
|
Sign up to set email alerts
|

Positive Feedback Within a Kinase Signaling Complex Functions as a Switch Mechanism for NF-κB Activation

Abstract: A switchlike response in nuclear factor-κB (NF-κB) activity implies the existence of a threshold in the NF-κB signaling module. We show that the CARD-containing MAGUK protein 1 (CARMA1, also called CARD11)-TAK1 (MAP3K7)-inhibitor of NF-κB (IκB) kinase-β (IKKβ) module is a switch mechanism for NF-κB activation in B cell receptor (BCR) signaling. Experimental and mathematical modeling analyses showed that IKK activity is regulated by positive feedback from IKKβ to TAK1, generating a steep dose response to BCR st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
107
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 91 publications
(118 citation statements)
references
References 34 publications
11
107
0
Order By: Relevance
“…Activation by trans-autophosphorylation is a positive feedback mechanism for a switch-like response to signal (Shinohara et al, 2014). By requiring the peripheral site to bind a PIP 3 for activation by dimerization, the Btk PH-TH module creates an even sharper PIP 3 concentration threshold for activation.…”
Section: Discussionmentioning
confidence: 99%
“…Activation by trans-autophosphorylation is a positive feedback mechanism for a switch-like response to signal (Shinohara et al, 2014). By requiring the peripheral site to bind a PIP 3 for activation by dimerization, the Btk PH-TH module creates an even sharper PIP 3 concentration threshold for activation.…”
Section: Discussionmentioning
confidence: 99%
“…The NF-κB system exhibits switch-like activation at the single cell level in B and T cells in addition to non-immune cells (Kingeter et al, 2010; Shinohara et al, 2014; Tay et al, 2010). We recently showed that integration of signal intensity and duration determines the probability of NF-κB switch activation (Kellogg et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…We found marked similarities in the gene-expression profiles of LMP2A-and BCR-activated B cells (Fig. S6) (47). However, quantitative analysis of these gene expressions will be required to confirm these possibilities.…”
Section: Discussionmentioning
confidence: 73%